Implementación de un sistema contable en el almacén Motoshopping de la ciudad de Loja, periodo abril – junio de 2014 - Cucalón Romero, Blanca Ivone (2015)
The thesis titled, IMPLEMENTATION OF AN ACCOUNTING SYSTEM IN THE WAREHOUSE MOTO SHOPPING LOJA CITY, April - June 2014 was conducted according to the regulations of the National University of Loja, before opting for the degree of Engineer in Accounting and Audit, the accounting system will allow recording, classifying, summarizing significantly and in terms of money, transactions and events that are at least of a financial nature, as well as to interpret its results for decision making. In compliance with the objectives of the thesis project plan and manual analysis, initial inventory was taken; the accounting process with the source documentation Initial Situation State with the values that make up the assets, liabilities and equity, journal in which transactions are recorded daily, general ledger; trial balance was used to check the balance of debits and credits; adjustments that facilitated present reasonable account balances of the financial statements in the period analyzed. In the development of investigative work as detected some shortcomings: lack of periodic inventories preventing determine the existence of merchandise at cost price to market. So you should periodically run the inventory of assets and values of the company Moto Shopping allowing proper control of goods for sale record of increases and decreases identified in each concept related to the purchaser Sale of Goods